Faktor-Faktor Yang Mempengaruhi Nilai Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2016-2020 - Dhahana, Sat Yudha; Salsabila, Utari Rahma; Taufik, Rukhiyat (JURNAL PELITA MANAJEMEN, 2023)
The purpose of this study is to determine the factors that affect the value of companies in manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2020 period involving 59 companies and the number of observations as many as 295 data. The data analysis method uses multiple linear regression. The results of the study found that profitability and company size have a positive and significant effect on the value of the company, this shows that profitability and company size are able to increase the value of the company. Debt to assets ratio and debt to equity ratio do not have a positive and significant effect and the company's growth does not have a negative and significant effect on the company's value, this shows that the debt to assets ratio, debt to equity ratio and company growth are not able to increase the company's value.